Tauroursodeoxycholic acid acts via TGR5 receptor to facilitate DNA damage repair and improve early porcine embryo development. Issue 1 (3rd December 2019) - Dicks, Naomi; Gutierrez, Karina; Currin, Luke; Priotto de Macedo, Mariana; Glanzner, Werner; Michalak, Marek; Agellon, Luis B.; Bordignon, Vilceu
Abstract: DNA damage associated with assisted reproductive technologies is an important factor affecting gamete fertility and embryo development. Activation of the TGR5 receptor by tauroursodeoxycholic acid (TUDCA) has been shown to reduce endoplasmic reticulum (ER) stress in embryos; however, its effect on genome damage responses (GDR) activation to facilitate DNA damage repair has not been examined. This study aimed to investigate the effect of TUDCA on DNA damage repair and embryo development. In a porcine model of ultraviolet light (UV)‐induced nuclear stress, TUDCA reduced DNA damage and ER stress in developing embryos, as measured by γH2AX and glucose‐regulated protein 78 immunofluorescence, respectively. TUDCA was equally able to rescue early embryo development. No difference in total cell number, DNA damage, or percentage of apoptotic cells, measured by cleaved caspase 3 immunofluorescence, was noted in embryos that reached the blastocyst stage. Interestingly, Dicer‐substrate short interfering RNA‐mediated disruption of TGR5 signaling abrogated the beneficial effects of TUDCA on UV‐treated embryos. Quantitative PCR analysis revealed activation of the GDR, through increased messenger RNA abundance of DNAPK, 53BP1, and DNA ligase IV, as well as the ER stress response, through increased spliced XBP1 and X‐linked inhibitor of apoptosis. Results from this study demonstrated that TUDCA activates TGR5‐mediated signaling to reduce DNA damage and improve embryo development after UV exposure. Abstract : This study demonstrates that tauroursodeoxycholic acid can reduce DNA damage and rescue development in embryos exposed to UV radiation. This study showed that activation of TGR5 pathways facilitates genome damage response and cell survival responses necessary for normal embryo development.